SamuderaMaps: water quality maps for marine and river ecosystems / Sharir Aizat Kamaruddin ... [et al.] - Kamaruddin, Sharir Aizat; Abd.Aziz, Khairul Naim; Roslani, Muhammad Akmal; Zainol, Zamzila Erdawati; Ahmad, Aziani; Tajam, Jamil (2022)
There is a lack of water quality maps available right now, especially in the northern regions of Malaysia. The goals of SamuderaMaps are to achieve the conservation of marine ecosystems and to improve the economic profits for rural communities. SamuderaMaps is developed by combining data on the most recent state of the water data with Geographic Information System (GIS) technologies. SamuderaMaps is a ready-made product that consists of water quality maps of physicochemical water parameters, including water nutrient parameters, covering the area of Sungai Kilim, Pantai Kok, Pulau Dayang Bunting, Pulau Tuba, and Sungai Merbok in Kedah. At a reasonable cost, SamuderaMaps offers a variety of maps in both paper and digital versions. These maps are designed to meet the needs of a diverse audience of customers, including social and economic players and local communities. In terms of the contribution that it can make, SamuderaMaps can help environmentalists monitor the levels of water quality in locations that are difficult to access or those that have a high degree of biodiversity. In addition, SamuderaMaps helps conduct site-selection analyses to promote the long-term sustainable development of mariculture regions, coastal tourism destinations, and fishing hotspots. SamuderaMaps is congruent with the Sustainable Development Goals established by the United Nations, particularly SDG 14: "Life below water," SDG 2: "Zero hunger," SDG 3: "Good health and well-being," and SDG 13: "Climate action."